Coming of age : na pintura contemporânea - Corujo, Cecília Andrade, 1990- (2016)
The following investigation – Coming of Age: in Contemporary Painting – initially addresses, in its first chapter, the artistic project which served as the origin point for the ensuing text. By means of a reflection about the appropriation of the imagistic references of different media, as well as of the artistic work’s transtextual nature, what is demonstrated here is an imagery which is mainly characterized for its young characters from movies and portraits of musicians. Following this presentation, an analysis is made about how the easy access to cultural goods has influenced my growing-up and my immersion in fandom communities of music and cinema. A notion of an everlasting reflexive identity construction is proposed throughout this brief personal narrative, an identity previously discussed in the works of Anthony Giddens (2001), Charles Taylor (1998) and Batista Ferreira (2009). This thematic exposition is followed by a formal analysis of the artistic project of this dissertation, a work that is developed as an installation, made of drawings and paintings depicting the human figure, as well as sentences that are written and drawn within the exhibition space. The second chapter concerns the coming of age concept through an analysis of the historical development of the literary genre Bildungsroman. This second moment seeks to understand the way in which personal growth and self-formation were explored in this type of narrative and how the destiny of a young protagonist was to become one of the greatest themes in the literary world. Lastly, by doing this study on the development of the aforementioned literary genre, we understand how these formation concepts have changed with time – from being seen as something finite, stable and one-dimensional to being perceived as something in permanent transformation, hard to be restrained, shelters to great contractions